The patron thief of bread eaudiobook - Eagar, Lindsay (Listening Library, 2022)
A beautifully crafted middle-grade novel spiced with magic—and gargoyles!—from the acclaimed author of Hour of the Bees and Race to the Bottom of the Sea. Fished from the river as an infant and raised by a roving band of street urchins who call themselves the Crowns, eight-year-old Duck keeps her head down and her mouth shut. It’s a rollicking life, always thieving, always on the run—until the ragtag Crowns infiltrate an abandoned cathedral in the city of Odierne and decide to set down roots. It’s all part of the bold new plan hatched by the Crowns’ fearless leader, Gnat: one of their very own will pose as an apprentice to the local baker, relieving Master Griselde of bread and coin to fill the bellies and line the pockets of all the Crowns. But no sooner is Duck apprenticed to the kindly Griselde than Duck’s allegiances start to blur. Who is she really—a Crown or an apprentice baker? And who does she want to be? Meanwhile, high above the streets of Odierne, on the roof of the unfinished cathedral, an old and ugly gargoyle grows weary of waiting to fulfill his own destiny—to watch and protect. Told in alternating viewpoints, this exquisite novel evokes a timeless tale of love, self-discovery, and what it means to be rescued.